Stereoselective binding of chiral drugs to plasma proteins - Shen Qi; Wang Lu; Zhou Hui; Jiang Hui-di; Yu Lu-shan; Zeng Su (Acta Pharmacologica Sinica; Vol 34, No 8 (August 2013): Acta Pharmacologica Sinica, 2016)
Chiral drugs show distinct biochemical and pharmacological behaviors in the human body. The binding of chiral drugs to plasma proteins usually exhibits stereoselectivity, which has a far-reaching influence on their pharmacological activities and pharmacokinetic profiles. In this review, the stereoselective binding of chiral drugs to human serum albumin (HSA), α1-acid glycoprotein (AGP) and lipoprotein, three most important proteins in human plasma, are detailed. Furthermore, the application of AGP variants and recombinant fragments of HSA for studying enantiomer binding properties is also discussed. Apart from the stereoselectivity of enantiomer-protein binding, enantiomer-enantiomer interactions that may induce allosteric effects are also described. Additionally, the techniques and methods used to determine drug-protein binding parameters are briefly reviewed.